(untitled) (REMUNOM, 2025)
This article critically analyzes the regulation of post-mortem organ donation in the Brazilian legal system, with emphasis on the legal and ethical limitations imposed by the requirement of family authorization, even in the presence of an explicit expression of the deceased’s will. The research covers the historical evolution of national legislation, with particular focus on Law No. 9.434/1997 and the operation of the National Transplant System (SNT), examining the compatibility between the current legal framework and the constitutional principles of human dignity and autonomy of will. The legal effectiveness of personal self-determination after death is discussed, especially in light of the high rates of family refusal that hinder the realization of donations. The analysis is enriched by international experiences, particularly from countries that adopt the presumed consent model, suggesting legislative alternatives that reconcile the system’s efficiency with respect for individual freedom. The methodology employed is qualitative, based on bibliographic review, and legislative, doctrinal, and comparative analysis.